LABORARTORY BRNO - Havlíček, Jan (Vysoké učení technické v Brně. Fakulta architektury)
Koncept galerie - chrámu. Silná nárožní hmota, hladká, nečleněná, pobízí pozorovatele k rozvahám o měřítku člověka, měřítku domu. Efekt umocňuje její betonový povrch s ušlechtilou texturou. Současně objekt uzavírá logicky předpokládanou blokovou zástavbu. Útroby chrání návštěvníka před rušnými silnicemi a na malé ploše skýtají velkorysé, leč jemné prostory výstav (1500m2). Dvojice racionálněji pojatých hmot po stranách, navazující na okolní domy, obsahuje jednak zázemí galerie a jednak prostory pro obchod, kavárnu a startovní ateliéry.

The concept: gallery ~ temple. Powerful corner mass, smooth, absent perforation, it pushes viewer to thinking about human scale and scale of a structure. The effect is strenghtened by it's concrete surface with noble texture. In adition, the object logially conceals exisitng development. Insides of the building protects the visitor from noisy streets and on a small area, they offer generous, yet subtle spaces of exhbition (1500m2). Two, more rational looking, masses, at sides of the main one, match, with their height and roof profile, surrounding buildings. These two contains service and administration areas on one hand and comercial space, café and workshops on the other.
LABORARTORY BRNO
Keywords: Galerie Laborartory Beton Brno; Gallery Laborartory Exhibition Concrete Brno Anteater